Ekstraksi Minyak Atsiri Kulit Jeruk Lemon (Citrus limon (L.) Burm.f.) dengan Pretreatment Microwave dan Distilasi Air-Uap - Elvianto Dwi Daryono; Dwi Ana Anggorowati; Firyaal Putri Verdina; Vina Nur Laily (Jurnal Teknik Kimia USU, 2023)
Lemon peel is a waste containing essential oils which can be used as an aroma enhancer in food and drinks as well as aromatherapy. This study aims to determine the effect of microwave pretreatment power and time on the extraction of lemon peel essential oil. The research phase began with microwave pretreatment, namely lemon peel was put into the microwave with pretreatment times of 2 minutes, 4 minutes, 6 minutes, 8 minutes, and 10 minutes with microwave power of 100 W, 200 W, and 300 W followed by water-steam distillation 150 g of lemon peel. Furthermore, the distillate is put in a separatory funnel for Â± 12 hours to separate the essential oil and water. The top layer is essential oil added Â± 5 g of sodium sulfate (Na2SO4) to adsorb water. The best conditions for the extraction process of lemon peel essential oil was at 300 W microwave power and 2 minutes of pretreatment which produces clear yellowish lemon peel essential oil with a distinctive lemon smell with a yield of 4.88%, limonene content of 27.501%, and refractive index of 1.48.